Factors affecting the prevalence of stress, anxiety, and depression in undergraduate Indian dental students - Abdul Ahad; Puneet Chahar; Ekramul Haque; Afshan Bey; Meena Jain; Waseem Raja (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The objective was to assess the prevalence and the associated demographic factors of stress, anxiety, and depression among undergraduate (UG) Indian dental students and determine whether the pattern is different in government-run institutions and those managed by private authorities. MATERIALS AND METHODS: A cross-sectional study was conducted among dental UG students from five dental colleges. Snowball sampling was used to approach 776 potential participants, resulting in a complete response from 507 students. The questionnaire consisted of demographic data; year of study; type of college; accommodation; and Depression, Anxiety, and Stress Scale (DASS)-42. Descriptive data and inferential statistics were obtained. Chi-square test was applied for categorical data to test for significance, and higher analysis was done using multiple linear regression. RESULTS: Females and males comprised 71.8% (n = 364) and 28.2% (n = 143) of the study population, respectively. The prevalence of anxiety was highest (66.86%, n = 339), followed by depression (57.39%, n = 291) and stress (43.99%, n = 223). In terms of severity also, anxiety was the most prevalent condition as more than one-fourth of the students presented with severe and very severe scores in this aspect (25.43%, n = 129) compared to depression (14.39%, n = 73) and stress (10.09%, n = 51). Regression analysis revealed age as a strong positive predictor for all the three conditions, while staying in the hostel was a positive predictor for anxiety and stress. Being female was also an independent predictor for the high prevalence of stress. CONCLUSION: Stress, anxiety, and depression are highly prevalent among Indian dental students. Clinical students and interns have a higher prevalence of stress than preclinical students. Age, being female, and staying in the hostel are positive predictors for the severity of stress. There is no significant difference between government and private colleges, regarding the prevalence of any psychological condition.